Pengaruh Jumlah Produksi, Kurs Dollar AS, dan PDB Pertanian Terhadap Impor Jagung Indonesia Tahun 1985-2012 - Indraswari, I Gusti Ayu Putri Anggara; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 2, Februari 2015 (pp.71- 137), 2015)
Indonesia is an agricultural country has abundant natural resources. This is evidenced by the state of fertile soil and supported by a tropical climate. Indonesia should put agricultural products as a major power. One of the agricultural products that could be developed into a mainstay is corn. Corn is also the food crops that have a strategic role in the development of agriculture and the economy of Indonesia. However, problems arise when domestic corn production has not been able to meet domestic needs and Indonesia to import maize. This study aims to determine the influence of production, United States dollar exchange rate and the GDP of agriculture to the import of maize in Indonesia. Techniques for analyzing data used in this study is the technique of multiple linear regression analysis and the results of this study indicate that the amount of production and the United States dollar exchange rate negative and significant, while the GDP of agriculture positive and significant on maize imports in Indonesia in 1985-2012.
Keywords: The Import of Maize; Production; U.S. Dollar Exchange Rate; the GDP of Agriculture